Nanofibrous yarn reinforced HA-gelatin composite scaffolds promote bone formation in critical sized alveolar defects in rabbit model. (1st October 2018) - Manju, V; Anitha, A; Menon, Deepthy; Iyer, Subramaniya; Nair, Shantikumar V; Nair, Manitha B
Abstract: Alveolar ridge resorption and crestal bone loss necessitate the use of bone graft substitutes for dental rehabilitation. The aim of this study was to compare the bone regenerative property of nanofibre incorporated two composite matrices (nanofibrous sheet layered matrix (CS-S) and nanofibrous yarn reinforced matrix (CS-Y)) in critical sized mandibular defect in a rabbit model (under load bearing scenario). Histological evaluation revealed continuous bone formation in the defect implanted with fibre reinforced scaffolds than those without fibres as well as commercial nanoHA-collagen graft. Interestingly, the mineralisation and the mineral density were significantly higher with nanoyarn reinforced scaffolds. Moreover, the compressive strength of new bone formed from CS-Y scaffolds was almost similar to that of native rabbit mandible. It can be concluded that the mechanical strength provided by three-dimensionally reinforced nanoyarns in the matrix could promote bone formation in load bearing mandibular region, and these can be proposed as a scaffold of choice for alveolar bone augmentation and dental rehabilitation.